Chickpea genetic resources and its utilization in India: Current status and future prospects - Singh, Mohar; Bhardwaj, C.; Singh, Sarvjeet; Panatu, Sweety; Chaturvedi, S. K.; Rana, J. C.; Rizvi, A. H.; Kumar, Neeraj; Sarker, Ashutosh (The Indian Journal of Genetics and Plant Breeding, 2017)
Chickpea is recognized as most nutritious pulse crop andwith respect to acreage, it ranks at the top among pulses inIndia. Realizing the significance of plant genetic resources,special efforts were made by the National Bureau of PlantGenetic Resources (NBPGR) to collect the chickpeagermplasm from different states of India including certainuseful introductions from other countries. A large numberof germplasm accessions including wild species werecharacterized and evaluated for various agro-morphologicaltraits using chickpea minimal descriptor.Thus, extensivegermplasm collections now exist in various gene banks ofthe world including India. As far as germplasm maintenanceis concerned, a core set developed by ICRISAT comprisingof 1956 accessions and mini core set of 211 accessionsrepresenting diversity for seed yield and its componenttraits. Further, core set developed by NBPGR consisting of1103 accessions extracted from 14651 accessions conservedin the Indian National Gene Bank revealed that 70% ofmaterials belong to Indian origin. The characterization andevaluation experiments of chickpea conducted across thecountry led to the registration of some unique germplasmaccessions for different trait of interest. However, usingcrop wild relatives, several interspecific crosses and advancepre-breeding lines were developed by the pulse researchinstitutions in India. The trait of interest incorporatedespecially from C. reticulatum, C. echinospermum and C.judaicum species for widening the genetic base of cultivatedgene pool. Some pre-breeding lines have been suggestedas useful donors in national chickpea crossingprogrammes.